Measuring the Acceptance of Open Access Scholarly Publications in Central Universities in Northeast India: An Evaluation Using Data Carpentry Tools - Saikia, Swagota; Basumatary, Nijwm; Verma, Manoj Kumar (Journal of Information and Knowledge, 2025)
The Open Access (OA) movement has significantly impacted scholarly communication by promoting the free exchange of knowledge. This study evaluates the OA contributions of three premier central universities in India’s Northeast—North Eastern Hill University (NEHU), Tezpur University (TZU), and Mizoram University (MZU)—from 2014 to 2023. The study examines the volume of OA publications, preferred OA routes (Gold, Green, Bronze, Hybrid), licensing preferences, and the role of funding agencies in OA adoption. Using data from the Scopus database and analysed through Data Carpentry tools, the results reveal that while Tezpur University has the highest number of OA publications, Mizoram University has the highest proportion of OA content relative to its total research output. The Gold OA route is the most preferred, with the CC-BY license being the dominant choice. Additionally, the study highlights that institutions receiving substantial government funding demonstrate stronger OA engagement, suggesting that financial support influences OA publishing practices. These findings provide insights into enhancing OA policies and strategies to maximise accessibility to research in Indian academic institutions.